Um olhar sobre o sertão brasileiro: Johann Emanuel Pohl, a sua descrição da capitania de Goiás e a sua construção do imaginário - Rosenthal, Frederico de Oliveira (2010)
This study aims to analyze the descriptions written in the diaries of the naturalist trevelers who have been in Goias during the first half of the nineteenth century. Understanding the way the urban cores of the region were represented by them in their main aspects such as the stops to resupply the expeditions, urban economics, labor relations and crime. Comprehending how the urban population of Goias was described in theses diaries, and what motivated these naturalists to describe the urban areas, since the quest for knowledge of the natural riches of Brazil was the main reason that brought these scientists to this region. As sources, they used the diaries of the leading naturalists such as Johan Emanuel Pohl, Auguste de Saint-Hilaire and George Gardner who were in Goias at the beginning of the nineteenth century, without letting the contribution from the diary of Luiz D’Aliancourt aside. Starting from these sources and the talkings with other authors, this study discusses in a critical way how the cities of the Brazilian backlands and, especially the ones in the interior of Goias, were depicted by these naturalists. “Journey to the interior of Brazil” by Pohl was the most remarkable work because it treats the urban issue in Goias more comprehensively. The analysis of Pohl’s work made it possible to notice that his nearness to the backcountry population was responsible for the development of distinctive reports and that all these diaries will make up sources of research for the history of culture in Goias.